Function (Oxford University Press, 2020)
Our vision is for FUNCTION to be the home for the best of physiology and pathophysiology or, in other words, function and malfunction. From organelles to organisms, Function seeks papers that contribute to defining the mechanistic basis of living systems in health and disease. Function aims to be a highly selective journal, publishing major advances that extend physiological understanding of biological function and the changes associated with disease states. Function provides a high caliber and broad spectrum open-access platform for researchers to publish their major advances in basic, translational, and clinical sciences. We value your science and want it shared with the global community. We are committed to providing authors a final decision after the initial review, even if some revisions are requested. While additional experiments may be requested by the reviewers, the final outcome of the experiments will not impact the acceptance of the article. Function publishes original full research articles, but also short Focus articles that report an important new observation, based on solid evidence, but without the full exploration required for a full paper. All full research articles will be accompanied by a perspective article, written by an acknowledged expert in the field. A new type of Evidence Review article, quoting only original papers, will be commissioned from leading experts, but suggestions for such articles are welcome. All scientific content published in the journal goes through a comprehensive, quick, and fair review process overseen by experts in the field, but in addition Function will also publish editorials and opinion pieces.